Effects of material uncertainties on vibration performance of cross laminated timber floors - Milojević Marija (Society for Materials and Structures testing of Serbia, 2021)
Variety of wood species and complexity of their structure make the reliable material properties of cross-laminated timber (CLT) difficult to obtain, which can lead to inaccurate prediction of CLT behavior. Due to high stiffness-to-weight ratio, CLT floors can suffer from vibration serviceability issues. This paper aims to quantify the uncertainties induced by material properties and investigate their effect on vibration performance of CLT floors. Analysis based on Monte Carlo simulations, considering material properties as random variables, is developed. Based on the conducted analysis, appropriate conclusions have been derived.